Peripheral nerve injuries in the pediatric population: a review of the literature. Part I: traumatic nerve injuries - Costales, Javier Robla; Socolovsky, Mariano; Sánchez Lázaro, Jaime A.; Álvarez García, Rubén (Child's nervous system, 2019)
Objective This article reviews the clinical results that can be obtained after repair of a traumatic peripheral nerve injury in the pediatric population. Methods A systematic review of the published literature has been made. Results Functional outcome after major nerve injuries is sometimes disappointing in adults. However, children have been reported to experience much better functional results after nerve repair than adults. Moreover, recovery generally is faster in children. The superior capacity of children’s central nervous system to adapt to external or internal environmental changes (neural plasticity) and the shorter recovery distance from the axon repair site to the target muscle are claimed to be crucial determinants of their favorable outcomes. Moreover, even in the pediatric population, it has been demonstrated that functional results are better the younger the patient is, including better clinical results in those injured in early childhood (< 6 years old) than in those injured in adolescence. Other favorable prognostic factors include the type of nerve injury (with complete transections doing less well than crush injuries) and the timing of surgery (with better outcomes after early repairs). Conclusions All efforts should be done to repair in a timely and adequate fashion traumatic peripheral nerve injuries in children, as the results are good.